Implementation of The Bandar Lampung City Regional Regulation Lampung Number 4 of 2024 about Protection and Fulfillment of The Rights of Persons with Disabilities Disability in The Political Policy Perspective Tanfidziyyah - Roja Akbar Alghani; Nur Rahmah; Frenki (NEGREI: Academic Journal of Law and Governance, 2026)
This study aims to examine the implementation of Bandar Lampung City Regulation Number 4 of 2024 on Protection and Fulfillment of the Rights of Persons with Disabilities, especially in providing accessibility to public facilities for persons with disabilities. This study is based on the limited availability of friendly and easily accessible public facilities for persons with disabilities in Bandar Lampung. The research method used is qualitative with a case study approach. Data were obtained through field observations and interviews with staff of the Social Service of Bandar Lampung City and the sub-district apparatus of Pahoman. The results show that local government has taken various efforts to fulfill the rights of persons with disabilities through social rehabilitation programs, vocational skills training, social assistance, and cooperation with the Ministry of Social Affairs. However, the policy implementation still faces several obstacles, such as limited accessibility facilities in public spaces, budget constraints, suboptimal inter-agency coordination, and uneven public understanding of the rights of persons with disabilities. This study concludes that there is a need to improve inter-agency coordination, strengthen oversight of policy implementation, and provide more accessible public facilities to realize inclusive public services for persons with disabilities.